Toxic Effects of Methyl Parathion on Antioxidant Enzymes and Acetylcholinesterase Activity in Freshwater Fish, Labeo rohita - Sivaperumal, P; Sankar, T V (Fishery Technology, 2025)
The lethal concentration (LC50) of methyl parathion and its effect on the lipid peroxidation and antioxidant enzyme systems are elucidated in Labeo rohita of size 75 Â± 6 g at 96 h exposure. The probit analysis showed that the lethal concentration (LC50) for 24, 48, 72 and 96 h were 15.5, 12.3, 11.4 and 10.2 mg l-1 respectively. Besides lipid peroxides (LPO), the toxicity effect was followed from the activities of liver antioxidant enzymes catalase (CAT, EC 1.11.1.6), glutathione peroxidase (GPx, EC 1.11.1.9), superoxide dismutase (SOD, EC 1.15.1.1) and glutathione S- transferase (GST, EC 2.5.1.18). The effect of methyl parathion on tissue glutathione content and the inhibition of brain acetylcholinesterase (AChE, EC 3.1.1.7) activities were also studied. The LPO level and GST activity increased five folds and two folds respectively on exposure to methyl parathion at 10.2 mg l-1. The SOD activity increased by seven fold compared to control. AChE activity was inhibited by 74% at a concentration of 1.8 mg l-1 and 90% at 5.4 mg l-1 signifying the effect of methyl parathion on the nervous system of fish. The study indicate that changes in antioxidant enzymes and decrease in the AChE activity can be used as biomarkers for monitoring toxicity due to methyl parathion exposure in aquatic organisms like fish.